NMR Solution Structure of the Neurotrypsin Kringle Domain, - Ozhogina, Olga A. (2008)
Neurotrypsin is a multidomain protein that serves as a brain-specific serine protease. Here we report the NMR structure of its kringle domain, NT/K. The data analysis was performed with the BACUS (Bayesian analysis of coupled unassigned spins) algorithm. This study presents the first application of BACUS to the structure determination of a (13)C unenriched protein for which no prior experimental 3D structure was available. NT/K adopts the kringle fold, consisting of an antiparallel β-sheet bridged by an overlapping pair of disulfides. The structure reveals the presence of a surface-exposed left-handed polyproline II helix that is closely packed to the core β-structure. This feature distinguishes NT/K from other members of the kringle fold and points toward a novel functional role for a kringle domain. Functional divergence among kringle domains is discussed on the basis of their surface and electrostatic characteristics.